Symbolic interactionism and career outsider: a theoretical perspective for career study - Barros, Leandro Eduardo Vieira (2019)
In this article we present a theoretical and methodological discussion for the study of career in the perspective of symbolic interactionism. A possible approach in this scope leads us to what can be termed as an outsider career. The outsider career consists of a concept developed by Becker¹ (2008), from which the individual is considered by the other members of society an "outsider" person for having an unconventional behavior. In this way, this approach to career study considers the individual's social context, their interactions, their characteristics and the process of labeling. The use of symbolic interactionism for the analysis of the outsider career implies their own theoretical and methodological perspective, opening up possibilities for new research with an interdisciplinary look, focused on the social context, considering all the social actors involved in the outsider career.